The Structure and Optical Properties of Ag doped CdO Thin Film Prepared by Pulse Laser Deposition (PLD) (Baghdad Science Journal, 2018)
At a temperature of 300 K, a prepared thin film of Ag doped with different ratios of CdO (0.1, 0.3, 0.5) % were observed using pulse laser deposition (PLD). The laser, an Nd:YAG in ?=1064 nm, used a pulse, constant energy of 600 mJ ,with a repetition rate of 6 Hz and 400 pulses. The effect of CdO on the structural and optical properties of these films was studied. The structural tests showed that these films are of a polycrystalline structure with a preferred orientation in the (002) direction for Ag. The grain size is positively correlated with the concentration of CdO. The optical properties of the Ag :CdO thin film we observed included transmittance, absorption coefficient, and the energy gap in the wavelength range of 300-1100 nm. The prepared films, direct energy gap is negatively correlated to concentration of CdO.